The quality of training at the SENA is achieved with high quality instructors - Ramírez Perdomo, Eber Fernando
The text presents a reflection on the role of institutional policies in the instructors’ selection, recruiting, training and evaluation, and the importance of their role in improving the quality of the training provided by the National Service of Learning, SENA. To understand the dimension of the topic, the study developed by the Organization for Economic Co-operation and Development (OECD) was taken into account, which presented the results of its research about the situation of teachers for all member countries. In the text, teachers are important to attract, train and retain effective teachers (2009), finding some reasons to understand the value of policies on instructors, giving clues about their orientation to really ensure the quality of training.